Adherence to intravenous chemotherapy and associated factors among patients with cancer at Hawassa University Comprehensive Specialized Hospital Cancer Treatment Center, Sidama Region, Southern Ethiopia - Bargude Balta; Alemayehu Delelegn; Gulema Demissie; Bedilu Deribe (PLoS ONE, 2025)
Background Medication adherence refers to how closely a patient follows the prescribed timing and dosage of their treatment. Adherence to chemotherapy is particularly complex and multifaceted, and it can have a significant impact on the effectiveness of the therapy. In Ethiopia, non-adherence to chemotherapy is on the rise, but there has been limited research specifically on adherence to intravenous (IV) chemotherapy. Objective This study assesses IV chemotherapy adherence and associated factors among cancer patients in the Sidama Region, southern Ethiopia. Methods A hospital-based cross-sectional study included a purposive sample of 413 cancer patients undergoing IV chemotherapy. The Morisky Medication Adherence Scale was used to measure adherence levels. Data analysis was performed using SPSS version 26, employing descriptive statistics such as frequency distribution, mean, median, and standard deviation to describe the characteristics and magnitude of IV chemotherapy adherence. Bivariable and multivariable logistical regression analysis was conducted to identify factors associated with IV chemotherapy adherence. Result The current study revealed that the overall magnitude of good adherence toward chemotherapy treatment among cancer patients was 176/413(42.6%), with a 95% CI of 38–47.9. The multivariable analysis identified several independent factors associated with IV chemotherapy adherence. These factors included being married (AOR = 3.2, 95% CI:1.3,8), employment as a government employee (AOR = 2.4,95% CI:1.3,4.5), availability of transportation (AOR = 5.5, 95% CI:2.1,14), Good social support (AOR = 2.1,95% CI:1.9,11.3) and having a curative goal of treatment (AOR = 1.7,95% CI:1.1,2.7). Conclusion In the current study, the magnitude of intravenous chemotherapy adherence among patients with cancer was low compared to published national and international findings. Possible contributing factors include marital status, employment, Transportation availability, and social support. Targeted measures are needed to improve adherence and, as a result, maximize therapeutic benefits.